Vulvar Adenocarcinoma With Pagetoid Spread: A Case Report - Kazuaki Nishimura; Seiji Kagami; Haruka Kajio; Tamaki Wada; Naoyuki Toki; Kiyoshi Yoshino (Cancer Reports)
ABSTRACT Background In rare cases, cancer cells adjacent to the skin migrate intraepithelially and reach the epidermis, presenting a histological appearance similar to that of Paget's disease; this phenomenon is termed pagetoid spread. Herein, we report a case of vulvar adenocarcinoma with pagetoid spread, in which the primary lesion could not be identified outside the vulva. Case An 84‐year‐old woman, presented with a 5‐cm tumor in the right vulva. Histopathological examination revealed atypical Paget cells. Immunohistochemical examination revealed that the cells were positive for CK20 and CK7 and negative for CDX2 and GCDFP15. Thus, it was determined that the tumor was not a primary extramammary Paget's disease, but a secondary extramammary Paget's disease with pagetoid spread. There were no masses in the anus, rectum, urinary tract, or vagina. Computed tomography scan revealed a right vulvar tumor and lymph node enlargement around the abdominal aorta, and the tumor was diagnosed as lymph node metastasis of vulvar adenocarcinoma associated with extramammary Paget's disease. Conclusion We report a rare case of vulvar adenocarcinoma with pagetoid spread.